Digital marketing training to optimize the marketing of UMKM products for Guntung village community - Ainun Jariyah; Cici Tania; Dina Nur Azizah; Dwi Rahmadita; Ella Jusnita; Nahfa Qastalam; Muhammad Syahrir; Rafton Fardisi; Sindi Ayu Indriyani; Zabila Hariska; Iful Rahmawati Mega (Universitas Muhammadiyah Magelang, 2024)
In the business world, marketing is a crucial aspect that cannot be overlooked. With the advancement of technology, marketing strategies have evolved towards a more modern approach. The villagers of Guntung still lack understanding of digital marketing, resulting in limited exposure of their products beyond their local area due to the reliance on word-of-mouth marketing. To optimize marketing efforts, a digital marketing training program is necessary to enhance the community's understanding of digital marketing. The primary objective of this program is to improve the community's ability to market their products through social media and the internet by creating engaging content. This program will employ a hands-on approach, involving direct training and simulations using computers and mobile devices. Upon completion of the training, participants are expected to acquire the knowledge and skills to conduct digital marketing, ranging from creating marketplace accounts to designing product logos.